2022
DOI: 10.1590/2177-9465-ean-2022-0006en
|View full text |Cite
|
Sign up to set email alerts
|

Sexual function, depressive symptoms and quality of life of people undergoing hemodialysis therapy

Abstract: Objective to analyze the correlation between sexual function, depressive symptomatology and quality of life of people on hemodialysis treatment. Method a cross-sectional study developed with 54 participants. Data collection occurred between the months of March and May 2020. The data were analyzed with the Mann-Whitney and Spearman Correlation tests, with a 95% confidence interval. Results the correlation between sexual function and depressive symptomatology was only clinically relevant for women (ρ= -0.724).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The pathophysiology of sexual dysfunction in adults receiving dialysis is complex (Johansen, 2020). It is stated that many factors, such as age, duration of dialysis treatment, comorbid diseases, depression, anxiety and sleep problems, may affect sexual dysfunction in dialysis patients (Cruz et al., 2022; Guven et al., 2018; Pyrgidis et al., 2021). It is also reported that long‐term chronic kidney disease, comorbid diseases and medication use may increase sexual dysfunction (Chou et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathophysiology of sexual dysfunction in adults receiving dialysis is complex (Johansen, 2020). It is stated that many factors, such as age, duration of dialysis treatment, comorbid diseases, depression, anxiety and sleep problems, may affect sexual dysfunction in dialysis patients (Cruz et al., 2022; Guven et al., 2018; Pyrgidis et al., 2021). It is also reported that long‐term chronic kidney disease, comorbid diseases and medication use may increase sexual dysfunction (Chou et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is stated in the literature that coping strategies may also be associated with sexual dysfunction in the general population (Crisp et al., 2015). In the literature, the studies explored the relationships between sexual dysfunction and depression, anxiety, and quality of life in adults receiving dialysis or with chronic kidney disease (Cruz et al., 2022; Guven et al., 2018; Jarullah et al., 2020). However, the relationship between coping strategies and sexual dysfunction has not yet been explored in adults receiving HD or PD.…”
Section: Introductionmentioning
confidence: 99%